ANALISA KARAKTERISTIK PENGGUNAAN JEMBATAN PENYEBERANGAN PADA DAERAH PERBELANJAAN DI JALAN JENDERAL SUDIRMAN KOTA PALEMBANG - Hariman Hakim Harahap (Jurnal Teknik Sipil dan Lingkungan, 2014)
Pendesrians bridge are the alternative facilities for pedestrians, due facilitate pedestrians crossing the highway without disrupting the smooth traffic flow. Pendesrians bridges can be found in big cities, like Palembang city. The purpose of this study is to knowing and analyze the effective and the factors that affect the use of Pendesrians briges by pedestrians. Researchers did a comparison on three bridges, Jenderal Sudirman street, Brige A in front of Maraton shopping at International Plaza shopping area, Bridge B in front of the Shopiemartin store, and Bridge C next to Masjid Agung Palembang at 16 Ilir shopping market area. This study starts from the literature study, geometrical collection and data pedestrian traffic. Data processing is performed to determine the effectiveness of the pedestrian bridge and the Analytical Hierarchy Process ( AHP ) to determine the order of the factors that affect the use of the pedestrian bridges and pedestrian bridges sequence is most frequently used by pedestrians. In the analysis results to the effectiveness of pedestrian bridges, to Bridge A, Bridge B and Bridge C are 95.84%. The results of the analysis from 100 respondents indicated that the main factors influencing the selection of the use of the pedestrian bridges security 35.95 % and comfort 29.06 %. whereas in terms of technical criteria, width of the bridge 33% and security posts 28%.